The Consequences of Pension Reform for the General Government Sector - Ancyparowicz, Grażyna (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
The social security reforms implemented against the background of deep imbalances in the labour market have generated a huge public debt, whose interest burden has been absorbing a growing part of state budget revenues. To reduce these expenses, some of the government’s tasks were transferred to local government. But in the absence of adequate financial resources this led to a sharp increase in debt in the local government sector. In 2009, the structural shortage of the general government budget was so large that the European Commission implemented an excessive deficit procedure against Poland, which remains in force. The reform of the open pension funds and other points of the fiscal consolidation program carry the promise that the budget target will be achieved in 2015. In the longer term, though, we should strive to increase inflows to the Social Insurance Fund instead of lowering the purchasing power of social security benefits.